? ~ 3.35 µm distributed-feedback quantum-cascade lasers with high-aspect-ratio lateral grating - Slight, T.; Tandoi, G.; Revin, D.; McKee, A.; Zhang, S.; Meredith, W.; Cockburn, J.; Ironside, Charlie (2011)
We report the development of room-temperature distributed-feedback quantum-cascade lasers operating in a single mode in the 3.34 to 3.35 μm wavelength range. First-order lateral gratings with high aspect ratio (the ratio between the grating etch depth and its period) were formed using inductively coupled plasma etching. The as-cleaved lasers emit in pulsed regime with a sidemode suppression ratio of up to 24 dB and a peak single-mode output power of 130 mW from a single facet.